Bile Salt Hydrolase Degrades β-Lactam Antibiotics and Confers Antibiotic Resistance on Lactobacillus paragasseri - Kusada, Hiroyuki; Arita, Masanori; Tohno, Masanori; Tamaki, Hideyuki (Frontiers in Microbiology, 2022)
Bile salt hydrolase (BSH) is a well-characterized probiotic enzyme associated with bile detoxification and colonization of lactic acid bacteria in the human gastrointestinal tract. Here, we isolated a putative BSH (LpBSH) from the probiotic bacterium Lactobacillus paragasseri JCM 5343T and demonstrated its bifunctional activity that allows it to degrade not only bile salts but also the antibiotic (penicillin). Although antibiotic resistance and bile detoxification have been separately recognized as different microbial functions, our findings suggest that bifunctional BSHs simultaneously confer ecological advantages to host gut bacteria to improve their survival in the mammalian intestine by attaining a high resistance to bile salts and β-lactams. Strain JCM 5343T showed resistance to both bile salts and β-lactam antibiotics, suggesting that LpBSH may be involved in this multi-resistance of the strain. We further verified that such bifunctional enzymes were broadly distributed among the phylogeny, suggesting that the bifunctionality may be conserved in other BSHs of gut bacteria‬. This study revealed the physiological role and phylogenetic diversity of bifunctional enzymes degrading bile salts and β-lactams in gut bacteria. Furthermore, our findings suggest that hitherto-overlooked penicillin-degrading activity of penicillin acylase could be a potential new target for the probiotic function of gut bacteria.